Manajemen Risiko Dan Strategi Mitigasi Risiko Keuangan Pada Ptpn Sinergi Gula Nusantara Di Kab. Takalar - Siskayanti; Wa Ode Rayyani (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to identify and analyze the financial risks faced by PTPN SinergiGula Nusantara in Takalar Regency, as well as to evaluate the mitigation strategies implemented to manage these risks. A descriptive qualitative approach was used, with data collected through observation, interviews, and documentation. The findings indicate that the company encounters several financial risks, such as sugar price volatility, dependence on local raw material supply, and the need for continuous investment in technology and human resources. To address these challenges, PTPN SGN has implemented various mitigation strategies, including production process optimization, strengthening partnerships with farmers, and improving operational efficiency through training and enhanced risk management systems. This study highlights the importance of integrating risk management into corporate governance to ensure financial stability and sustainability in the national sugar industry. Strategic recommendations are proposed to enhance financial risk management and support the company’s sustainable growth.